Kajian Orientalis Terhadap Sanad dan Matan Hadis sebagai Sumber Hukum Islam - Ahmad Hikmi (Kosmik Hukum, 2021)
Orientalist studies of Islam and hadith have generated mixed responses from Muslims. Some were loud, extreme and quite harsh by rejecting the studies conducted by the Orientalists. However, some other Muslims are gentler by taking the positive side of the studies they have carried out, namely that they can contribute to Islamic knowledge and assets and also study of hadith in particular. Several names emerged which were later considered as orientalists who were quite intense in studying Islam and hadith, they were: Ignaz Goldziher, Duncan Black, Carl Becker, Snouck Hurgronje, and Louis Massignon, A.J. Wensinck, G.H.A. Joynboll, Daniel W. Brown, Alois Sprenger, Sir Willian Muir, A. Guillaume, S. Mackrnsen Ruth, J. Schact, and others. The orientalists who departed from a skeptical attitude began to cause uproar among Muslims by saying that the hadith was only made by the Companions and not from the Prophet. They also criticize the hadith in terms of sanad or matan, whose authenticity is still considered very dubious and lean made by certain parties.Keywords: orientalis, critic, sanad, Matan